Sabrina Coast (East Antarctica) depositional processes highlightedthrough stratigraphic and paleoenvironmental diatom analysis - Raffaella Tolotti; Meghan Duffy; Isabel Dove; Meaghan Kendall; Federica Donda; Roberto Romeo; Riccardo Geletti; Andrea Caburlotto; Leanne Armand; Phil O’Brien; Amy Leventer; Laura De Santis; et al. (European Geophysical Society, 2019)
The systematic survey of Antarctic margin sedimentary sequences offers, especially in poorly investigated areas,the opportunity to obtain a wide range of information on glacio-eustatic, climatic, and tectonic events. Multi-disciplinary datasets resulting from geophysical surveys and scientific coring and drilling are needed to addressquestions regarding the orbital forcing and the global response of the hydrosphere (oceans and atmosphere),cryosphere, and biosphere. The PNRA Tytan Project, embedded into the Australian project “Interactions of theTotten Glacier with the Southern Ocean through multiple glacial cycles” (Australian National University), aimsto understand how the Totten Glacier behaved during past Holocene and Pleistocene times of warmer climate.Insights for reconstructing the depositional and hydrodynamic environments of the continental margin off theTotten Glacier, a large outlet glacier located on the Sabrina Coast of East Antarctica, are addressed throughmicropaleontological efforts. The micropaleontological research group focused on identification of diatombiostratigraphic markers and assemblage analyses in sediment cores collected from the Sabrina Coast continentalslope during the RV Investigator mission IN2017_V01 in order to reconstruct paleoenvironments and to place ageconstraints on the sedimentary sequences.All but one of the piston cores recovered late Pleistocene sediments, documenting MIS 9 – MIS 1, withinterglacial intervals characterized by diatomaceous sediments dominated by the open water taxon Fragilariopsiskerguelensis. Glacial intervals have much lower diatom concentrations and a higher proportion of reworked forms.A single piston core, IN2017_V01_PC03, recovered a more complicated sedimentary sequence. This sequence,targeted for an older and more condensed coring location, was selected for coring based on the sub-bottomgeophysical data that indicated thinning of the upper stratigraphic section, and greater access to the underlyingsection. The results suggest a very dynamic ...